Analisis Pendapatan Usahatani Kacang Tanah (Arachis Hypogaea, L.) di Kelurahan Wailiti Kecamatan Alok Barat Kabupaten Sikka - Selfianus; Yohana Angreani (Fakultas Pertanian, Universitas Nusa Nipa, 2024)
This study aims to determine the income of peanut farming in Wailiti Village, West Alok District, Sikka Regency. The results indicate that the average income is Rp 426,146, the highest income from peanut farming is Rp 2,284,750, and the lowest income is Rp 25,500. The R/C ratio for peanut farming is 1.5, which, according to the criteria of an R/C greater than 1, is considered feasible. Therefore, peanut farming in the study area can be considered feasible.